The Study of Law at the University of the South Pacific - Angelo, A H; Goldring, J (Victoria University of Wellington Law Review, 1994)
A number of developments of interest to the countries of the South Pacific took place at the University of the South Pacific in the 1990s. In this article, two lawyers who have had some involvement with those developments provide a brief report on what happened. The article first covers the background and history of the University, the development of law programmes in the University (including the introduction of the LLB degree in 1994), and future developments for the University’s law programme on the horizon. This article also includes an appendix which includes the University of the South Pacific’s LLB degree curriculum as at 1994.